Water-in-diesel fuel nanoemulsions: Preparation, stability and physical properties - M.R. Noor El-Din; Sabrnal H. El-Hamouly; H.M. Mohamed; Marwa R. Mishrif; Ahmad M. Ragab (Egyptian Journal of Petroleum)
In this work, water-in-diesel fuel nanoemulsions were prepared with mixed nonionic surfactants. Several mixtures of sorbitan monooleate and polyoxyethylene (20) sorbitan monooleate, with different Hydrophilic–Lipophilic Balance (HLB) values (9.6, 9.8, 10, 10.2 and 10.4) were prepared to achieve the optimal HLB value. Three mixed surfactant concentrations were prepared at 6%, 8% and 10% to identify the optimum concentration. Five emulsions with different water contents: 5%, 6%, 7%, 8% and 9% (wt./wt.) were prepared using high energy method at the optimum conditions (HLB = 10 and mixed surfactant concentration = 10%). The effect of HLB value, mixed surfactant concentration and water content on the droplet size has been studied. The interfacial tension and thermodynamic properties of the individual and the blended emulsifiers were investigated. Droplet size of the prepared nanoemulsions was determined by dynamic light scattering and the nanoemulsion stability was assessed by measuring the variation of the droplet size as a function of time. From the obtained results, it was found that the mean droplet sizes were formed between 49.55 and 104.4 nm depending on HLB value, surfactant concentration and water content of the blended emulsifiers. The physical properties, kinematic viscosity and density, of the prepared nanoemulsions and the effect of different temperatures on these properties were measured.